THE POLITICAL DISCOURSE OF NATION AND COUNTRY IN THE PRESS OF THE INDEPENDENCE PROCESS OF PERU (1821-1822) (Tzintzun, Revista de Estudios Históricos, 2022)
The article analyzes the discursive constructions that show the configuration of a macro-identity of the Peruvian homeland or nation in the context of the crisis of the final period of the Viceroyalty of Peru in four of Lima’s newspapers that represented some of the dominant political positions: a loyal envisioned newspaper like El Triunfo de la Nación; another with a patriotic position and favorable to the constitutional monarchy, such as Los Andes Libres, whose continuation was the Correo Mercantil Politico y Literario; and a pro-independence and republican newspaper such as La Abeja Republicana. The research maintains that the discursive construction of patriotism started from a purely emotional and affective consideration, in which passion stood out as a guide to that feeling; however, this patriotism could only be guided by the abstract idea of a nation (a territory, a population and an idea) with which the citizens of the arising Peruvian republic should feel identified.
Keywords: nation; homeland; independence; Peru; speech